Pelatihan Modul Ajar Robotika Berbasis Visual Basic Di SMP Swasta Assyuhada Medan - Fadhillah Azmi; Juanda Hakim Lubis; Dharshini N P (Pelita Masyarakat, 2019)
The teachers of SMP Swasta Assyuhada Medan have difficulty in applying practicum and application to local electronic content subjects that can be assessed as innovative work and development for students. This situation is caused by teachers who still lack direct funds when buying or facilitating equipment used. The purpose of this activity is that the trainning of SMP Swasta Assyuhada Medan in carrying out their duties have the capability of learning media simulation techniques as innovative works so as to increase professionalism on an ongoing basis. The method used is in the form of training robotics learning modules using simulations from Visual Basic. This community service activity is expected to succeed so that at the end of the activity all the training participants have the knowledge and skills about giving lab work to students so that the children can get more creative ideas